The challenges of the Family Health Strategy in the incidence of congenital syphilis in Pernambuco, Brazil, between 2009 to 2018 - Farias, Maria Lua Santos Alves de; França, Bruna Stefany Rebouças; Soares, Maryanne Ferreira; Machado, Michael Ferreira (ABCS Health Sciences, 2023)
Introduction: Syphilis is a health problem and an issue for maternal and child health. Objective: To analyze the incidence of congenital syphilis (CS) and its relationship with the Family Health Strategy (FHS) in the state of Pernambuco, between 2009-2018. Methods: Observational analytical retrospective study with secondary data provided by the Brazilian National Notifiable Diseases System of the Ministry of Health on syphilis infection during pregnancy, congenital syphilis, and FHS coverage information, made available on the e-Gestor AB platform, between 2009-2018. Microsoft Office Excel, JASP 0.14.1.0 and Statistical Package for the Social Sciences 25 programs, and Shapiro-Wilk test, Spearman, and Chi-Squared test were used for the organization and analysis of sociodemographic and clinical variables. Results: 11,519 cases of CS were reported in Pernambuco between 2009-2018, with a 12% increase in the FHS coverage rate in the state and 376% growth in the detection rate of CS per thousand live births in the analyzed period. Of the maternal sociodemographic characteristics, there was a higher occurrence of infection in women aged 20 to 29 years (52.76%), black (77.53), and incomplete elementary school or no education (49.56%). In 90.29% of the cases, recent congenital syphilis was identified as the final diagnosis. The analysis also revealed that the greater the FHS coverage in the state, the greater the amount of inadequately performed treatments. Conclusion: The analysis of CS cases related to the FHS point to weaknesses in the control and proper treatment of the disease, especially in Black women with low education.